DAMPAK PENGARUH BBM TERHADAP SEKTOR EKONOMI UMKM DI SERANG - Vera Maria (Jurnal Inovasi Penelitian, 2023)
The increase in fuel oil is a policy taken by the government for reasons that cannot be separated from the increase in world oil prices and the state budget deficit, the increase in world oil and the occurrence of a state budget deficit by a country that this is reason why the price of fuel oil is increased, if seen from one side, maybe the government's decision to increase the price of fuel oil is right. However, the government should also pay attention to the condition of the small community even though the government realizes that Indonesia is one of the poorest countries with tens of unemployed people. Therefore, the government should be more realistic. Fuel oil (BBM) is an important component in the process of sustainability for MSMEs. When fuel prices rise, MSMEs generally reduce labor costs as an indicator of production which results in lower production volumes. However, most MSMEs do not seek to increase selling prices, namely by using the strategy of reducing the size of goods, reducing product quality, reducing business profits, and making production cost efficiencies